La Dolce Hood: Rethinking Hip-hop Masculinity through Italian Cinema and Fashion. The Case of Vibe Magazine. 1992–1997 - Gatti, Giuseppe (ZoneModa Journal, 2024)
The essay explores the intersections between Italian film, fashion, and hip-hop “Golden age” masculinity from 1992 to 1997, with a specific focus on Vibe magazine. Through an analysis of Vibe’s coverage of hip-hop and fashion, I argue that the representation of hip-hop masculinity in Vibe was shaped by sampling both American and Italian cinematic and cultural tropes (specifically Hollywood musicals, spaghetti westerns and gangster movies). The essay examines how Vibe’s portrayal of hip-hop masculinity through sophisticated fashion services, crafted and intercepts broader cultural and visual trends over hip-hop, proposing an alternative and progressive vision of black male identity in respect of the toxic image of “gagsta rapper” and its associated racial tropes. Combining original archival perusal and interviews with an action-network oriented methodology, the essay retraces the complex and often ambiguous nature of hip-hop masculinity, as well as how cultural cross-pollination might orient our understanding of hip-hop, gender and national identity.